Selected papers on the periodic table - Scerri, Eric R. (Imperial College Press ; Distributed by World Scientific Pub. Co., 2009)
This book contains key articles by Eric Scerri, the leading authority on the history and philosophy of the periodic table of the elements and the author of a best-selling book on the subject. The articles explore a range of topics such as the historical evolution of the periodic system as well as its philosophical status and its relationship to modern quantum physics. This volume contains some in-depth research papers from journals in history and philosophy of science, as well as quantum chemistry. Other articles are from more accessible magazines like American Scientist. The author has also provided an extensive new introduction in order to integrate this work covering a period of two decades. This must-have publication is completely unique as there is nothing of this form currently available on the market.